Epidemiology of injuries in National Collegiate Athletic Association men's track and field: 2014-2015 through 2018-2019 - Boltz, A. J.; Roby, P. R.; Robison, H. J.; Morris, S. N.; Collins, C. L.; Chandran, A. (Journal of Athletic Training, 2021)
Context: Women's track and field events at the National Collegiate Athletic Association level have grown in popularity in recent years, and track and field athletes are vulnerable to a broad range of potential injuries. Background: Routine examination of track and field injuries is important for identifying emerging patterns in injury incidence. Methods: Exposure and injury data collected in the National Collegiate Athletic Association Injury Surveillance Program during the 2014-2015 to 2018-2019 academic years were analyzed. Injury counts, rates, and proportions were used to describe injury characteristics, and injury rate ratios were used to examine differential injury rates. Results: The overall injury rate was 2.20 per 1000 athlete exposures; the competition injury rate was higher than the practice injury rate (injury rate ratio = 1.73; 95% confidence interval = 1.51, 1.97). Hamstring tears (8.9%), medial tibial stress syndrome (5.4%), and lateral ligament complex tears (4.2%) were the most reported injuries. Conclusions: Given the results of this study, further attention may be directed toward factors associated with noncontact injury risk in the competitions. The changing injury rates of most reported injuries also warrant monitoring post 2018-2019.